Known species and new records of Coronophorales (Ascomycota) in Mexico - Chacón Zapata, Santiago; Ramírez-Guillén, Florencia (Instituto de Ecología, A.C., 2022)
Background and Aims: The order Coronophorales has been poorly studied in Mexico. It includes six families, but only four of them are represented in the country. It is characterized by turbinate or globose perithecial ascomata, with the presence or absence of quellkörper structures and/or Munk pores. The objective of this work is to present the species of Coronophorales previously known for the country and to describe the new records. Methods: Random explorations were carried out to collect specimens, between 2011 and 2015, in urban and peri-urban green areas of the city of Xalapa, Veracruz, Mexico. Material collected and previously herborized was reviewed. The study of the samples was done according to traditional techniques in mycology and all the material studied is deposited in the herbarium XAL. Key results: Eleven species of Coronophorales are described. Nine of these are new records for Mexico: Bertia sinensis, B. triseptata, Chaetosphaerella fusca, Fracchiaea callista, Gaillardiella pezizoides, Nitschkia collapsa, N. floridana, Tympanopsis confertula and T. uniseriata; Fracchiaea broomeana is recorded for the first time from Veracruz and Nitschkia grevillii is recorded from new locations. Drawings or photographs of the studied material are presented, as well as a key to determine all the species of the order known so far in the country. Conclusions: The order Coronophorales is little represented in Mexico. Prior to this contribution, ten species of the group were known; however, with the new records presented here, there are now 19 known species of this group of fungi in the country.